(untitled) (Research, Society and Development, 2021)
Objectives. To describe dental students’ knowledge, regarding the COVID-19 pandemic in dental care as to biosafety rules and protocols in force. Method. This was a sectional, descriptive study. The sample was composed of dental students from 8 universities, public and private, located in the state of Rio de Janeiro. A structured questionnaire was applied on line with questions about demographic data, aspects associated with biosafety in dental practice and, finally, perceptions regarding COVID-19. Undergraduate students who were in the preclinical periods were excluded. Results. A total of 123 students, predominantly female (85.37%), participated. The mean age of the participants was 27.24 years, 69.92% with ages ranging from 19 to 26 years, most of them attending the last periods of Dentistry undergraduate studies (63.42%) in private universities (88.62%). All participants recognized the signs and symptoms of the disease, fever and shortness of breath being the most frequently mentioned symptoms. About 67.48% of the respondents do not feel safe to attend patients with minimal risk of contamination by COVID-19, even with knowledge of biosafety. Conclusion. The undergraduate students recognize the main signs and symptoms of COVID-19 and the biosafety aspects practiced by them are within the prerogatives for infection control in university clinics.